A Research Model for the Study of Interpersonal Communication Competence - Cegala, Donald J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
The purpose of this paper is to present a general research model for the study of interpersonal communication competence. The paper summarizes the research background for the model and covers considerations for a general theory of competence. It notes that recently the communication field has shifted in emphasis from concerns of public speaking competence to research and theory about competence in small groups, organizational settings, the family, and interpersonal settings. It explains that there is a lack of consensus about a general theory of competence, and therefore, little to guide researchers in selecting and evaluating dimensions of communicative competence. The paper finds that the literature consists of numerous proposed dimensions, but that few of these have undergone rigorous assessment and evaluation. In noting considerations for a general theory, it advocates combining knowledge of how to behave with actual performance in order to distinguish competence, and argues that competence also implies standards of appropriateness and effectiveness. The paper then describes a study that used the model to collect data on interaction involvement, concluding that the model reveals the utility of pursuing such studies. (CRH)
ERIC Note: Paper presented at the Annual Meeting of the Speech Communication Association (69th, Washington, DC, November 10-13, 1983).
Microfiche.
Keywords: Communication Research; Communication Skills; Communication (Thought Transfer); Interpersonal Communication; Interpersonal Competence; Models; Research Design; Research Methodology; Research Needs; Speeches/Meeting Papers; Reports, Descriptive; Information Analyses